Alcohol-Related Traffic Accidents Resulting in Death: Analysis of Driver Negligence and Liability: Kecelakaan Lalu Lintas Akibat Alkohol yang Menyebabkan Kematian : Analisis Kelalaian dan Pertanggungjawaban Pengemudi - Abdullah, Reza; Sudiro, Amad (Indonesian Journal of Law and Economics Review, 2025)
Background (General): Traffic accidents in Indonesia continue to rise annually, creating serious social and economic impacts. Background (Specific): A significant number of fatal accidents are caused by drivers operating vehicles under the influence of alcohol, as illustrated in the Pekanbaru case involving multiple deaths. Knowledge Gap: However, comprehensive legal analysis on the classification of negligence and the extent of criminal liability for alcohol-related fatal accidents remains limited. Aim: This study aims to examine the legal categorization of negligence (culpa) and determine the scope of driver criminal responsibility when drunk driving results in loss of life. Results: Findings show that such cases fall under culpa lata or gross negligence, as the drivers consciously continue driving despite clear foreseeable risks, thereby meeting the legal elements of criminal negligence under Indonesian criminal and traffic law. Novelty: The study provides an integrated doctrinal and empirical analysis linking legal theory, statutory frameworks, and real case application, particularly emphasizing the application of dolus eventualis in traffic negligence. Implications: The research underscores the importance of stricter enforcement and legal awareness to enhance road safety and strengthen public protection through more effective criminal accountability mechanisms. Highlights: Highlights the legal classification of drunk-driving fatalities as culpa lata (gross negligence). Demonstrates how foreseeability and lack of caution shape criminal liability. Emphasizes the need for stronger enforcement to protect public safety. Keywords: Traffic Accidents, Alcohol, Negligence, Criminal Liability, Indonesia